2018
DOI: 10.3847/2041-8213/aac48a
|View full text |Cite
|
Sign up to set email alerts
|

Possible Accretion Disk Origin of the Emission Variability of a Blazar Jet

Abstract: We analyze X-ray light curves of the blazar Mrk 421 obtained from the Soft X-ray Imaging Telescope and the Large Area X-Ray Proportional Counter instrument onboard the Indian space telescope AstroSat and archival observations from Swift. We show that the X-ray power spectral density (PSD) is a piece-wise power-law with a break, i.e., the index becomes more negative below a characteristic "break-timescale". Galactic black hole X-ray binaries and Seyfert galaxies exhibit a similar characteristic timescale in the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 52 publications
7
29
0
Order By: Relevance
“…The variability thus is indicative of essentially "pink/flicker noise" type at these higher frequencies of the electromagnetic spectrum. We note that the PSD slopes derived here for the Xray light curves are in good agreement with β ∼1.2-1.5 reported in Isobe et al (2015); Chatterjee et al (2018) for the blazar Mrk 421. Similarly, the PSD slopes derived at VHE and HE γ−ray light curves by means of the DFT method, are in good agreement with β ∼1.2 and ∼1.1 reported in (Table 1).…”
Section: Resultssupporting
confidence: 90%
“…The variability thus is indicative of essentially "pink/flicker noise" type at these higher frequencies of the electromagnetic spectrum. We note that the PSD slopes derived here for the Xray light curves are in good agreement with β ∼1.2-1.5 reported in Isobe et al (2015); Chatterjee et al (2018) for the blazar Mrk 421. Similarly, the PSD slopes derived at VHE and HE γ−ray light curves by means of the DFT method, are in good agreement with β ∼1.2 and ∼1.1 reported in (Table 1).…”
Section: Resultssupporting
confidence: 90%
“…While such a break has not been found in the power spectra of the emission variability in many blazars it has been observed in a few cases. Most recently Chatterjee et al (2018) have confirmed the presence of a break in the X-ray power spectral density of the blazar Mrk 421, which was previously hinted by other authors (Kataoka et al 2001;Isobe et al 2015). Goyal et al (2018) have inferred a break time-scale in the γ-ray variability of another BL Lac object OJ 287 from their analysis of its Fermi-LAT light curve.…”
Section: Introductionsupporting
confidence: 55%
“…Alternatively, similar PSDs at different wavelengths might only imply a common origin of the variability, as would be the case in the inner propagating fluctuations model. PSD breaks on the order of days have been detected in several of our sources in the X-ray (Kataoka et al 2001(Kataoka et al , 2002McHardy 2008;Chatterjee et al 2018) and the extreme ultraviolet (Cagnoni et al 2001). The γray PSDs are all close to the measurement noise level at these timescales, however, so detection of similar breaks was not possible.…”
Section: Origin Of Variability Timescalesmentioning
confidence: 80%